An assessment of the institutional preparedness of the local government of Carles, Iloilo in implementing a sustainable coastal resource management program - Manggasang, Julieto A. (University of the Philippines in the Visayas, 2003)
An institutional preparedness assessment of the local government unit of Carles for a sustainable coastal resource management program implementation was conducted utilizing a SWOT analysis. A questionnaire was formulated to gather primary data that is perception-based. The officers and members of the Carles Miunicipal Fisheries and aquatic Resources Management Council served as the study repsondents. A validation of the survey results and the subsequent indentification of present and potential issues and problems that may hinder the successful implementation of CRM Porgram, as well as the alternatives to address these was conducted through a workshop. The institutional preparedness of the LGU in implementing and managing A CRM program was assessed based on hte administrative, financial and technical capability levels with its corresponding indicators, to wit: CRM concept awareness and organizational participation, political will and leadership, CRM policy formulation and implementation, adequacy of equipment and facilities, and values and attitudes of stakeholders (administrative); availability of financial resources/fnancial generation capacity (financial); and, aavailability of knowledgeable or skilled personnel (technical expertise), and linkage/partnership with other institutions (for technical). Study results derived according to the perception of the respondents show that the LGU of Carles is institutionally prepared to implement nd manage a sustainable CRM program. Its strengths lie in the area of administration - CRM concept awareness and organizational participation. However, sufficient allocation must be given to implement and sustain the operations of a CRM program. Along this line, the LGU may need to review its financial management system to ensure continuous local funding for the CRM activities. Furthermore, LGU weaknesses are perceived to be seen in areas of political will and support of CRM activities blocal leaderships, inadequate facilities and equipment, and linkages or partnership with other institutions. Oppurtunity is seen in the aspect of developing a viable and sustainable agri-based industry. Changing policies and the manner that these are implemented at both the national and local levels are considered as threats.The study recommends a vigorous IEC campaign on CRM concepts, fishery laws and ordinances towards increased levels of compliance Community mobilization and people empowerment remain the major strategies in the implementation and management of CRM program in the municipality of Carles.